Penggunaan Model Open Ended dalam Pembelajaran Matematika untuk Meningkatkan Kemampuan Berfikir Kreatif Siswa Kelas V - Imelda, Suci; Siagian, Fitri Nauli; Shalahudin (IBTIDA', 2024)
The mathematics learning process currently taking place in the field has not been able to facilitate students' creative thinking abilities. Mathematics learning emphasizes aspects of conceptual understanding rather than procedural assignments. Apart from this, in learning mathematics students are also less active and students only usually solve mathematics problems like the examples the teacher gives which are closed in nature. There are many aspects that cause students' creative mathematical thinking abilities to be less than optimal. The main factor is students who are not used to working on higher-level thinking questions, one of which is open-ended or open-ended mathematics questions. This research aims to find out how the use of the open end model can improve students' creative thinking abilities, how students respond to the use of the open end model in mathematics learning and whether mathematics learning using the open end model can improve students' creative thinking abilities. This research uses the Classroom Action Research (PTK) method, data collection instruments using test questions, observation sheets (teacher activities and student activities), interviews and documentation. The results of the research show that there is an increase in students' creative thinking abilities by using the open end model in mathematics learning. This can be shown by the increase in the percentage score for each indicator in cycle I and cycle II. A cycle or round in PTK is a one-time learning process in accordance with the plan that has been prepared. Teacher activity observations in cycle I were 68.42%, increasing to 85.26% in cycle II and observations of student activity in cycle I were 76.47% to 89.41. % in cycle II.